Prostate carcinogenesis induced by N-methyl-N-nitrosourea (mnu) in gerbils: Histopathological diagnosis and potential invasiveness mediated by extracellular matrix components - Goncalves, Bianca F. [UNESP]; Zanetoni, Cristiani; Scarano, Wellerson R. [UNESP]; Goes, Rejane M. [UNESP]; Vilamaior, Patricia S. L. [UNESP]; Taboga, Sebastiao R. [UNESP]; Campos, Silvana G. P. [UNESP] (Academic Press Inc. Elsevier B.V., 2010)
In the present study prostate lesions were induced in gerbils (Meriones unguiculatus) treated with a single N-methyl-N-nitrosourea (MNU) dose; thus, the incidence, latency and histology of these lesions were evaluated. Fibrillar elements of the extracellular matrix associated with microinvasive sites were also investigated. Animals were divided into 5 groups, including 2 control groups: (1) remained untreated; (2) received the corn oil vehicle (vehicle, 0.1 ml/application) and three different tumor induction regimens: (1) received MNU (30 mg/kg) and weekly testosterone (2 mg/kg) (MNU + testosterone); (2) received only MNU (30 mg/kg); (3) received weekly testosterone doses (2 mg/kg). After 3 and 6 months the animals were dissected and the prostates were evaluated morphologically, immunohistochemically and quantitatively. MNU plus androgen contributed to the development of prostatic intraepithelial neoplasia, microinvasive carcinoma and adenocarcinoma in gerbil prostate. However, these lesions occurred earlier in time in groups that received MNU and androgen compared to control animals as they over time also developed to a high extent microinvasive lesions. Cytochemistry and immunohistochemistry showed that these injuries were commonly associated with inflammatory cells whereas the epithelial cells presented proliferative activity. The alpha-methylacyl-CoA racemase (AMACR) expression in prostate cancer cells facilitated diagnosis of gerbil lesions. Testosterone, MNU and MNU + testosterone showed an increased epithelial volume, although the secretory activity was significantly suppressed mainly at neoplastic foci. In the prostatic stroma, reticular fibers increased significantly in MNU, MNU + testosterone and among the lesions found in these groups, while collagen fibers decreased at neoplastic sites. The disruption of the basement membrane was proven at malignant sites by ultrastructural analysis and type IV collagen and laminin degradation. The prostate carcinogenesis mediated by MNU and androgen stimulated the emergence of proliferative lesions in gerbils after short periods and showed the importance of a dynamic remodeling of stromal components for cellular invasiveness. Published by Elsevier B.V.
Keywords: MNU; Testosterone; Prostate cancer; alpha-Methylacyl-CoA racemase; Extracellular matrix; Gerbil